Applied corporate finance - Damodaran, Aswath
Applied Corporate Finance, Second Edition converts the theory and models in corporate finance into tools that can be used to analyze, understand, and help any business. With this hands-on guide, you can find real solutions to real corporate finance problems, using real-time data